Returns-to-scale properties in DEA models: The fundmantal role of interior points - Vladimir Krivonozhko; Finn R. Førsund (University of Oslo, Department of Economics, 2009)
Attempts can be found in the DEA literature to identify returns to scale at efficient interior points of the production possibility set on the basis of returns to scale at points of the corresponding reference sets. However, an opposite approach is put forward in this paper, advocating that returns-to-scale properties of efficient reference units should be found by identifying first returns to scale of an efficient interior unit that is a radial projection to the frontier of an inefficient unit. Returns-to-scale properties of both the corresponding reference units and units supporting the face in question can then be established.
Keywords: C61; D20; 330; Returns to scale; DEA; Interior points; Vertices; Skalenertrag; Data-Envelopment-Analyse; Mathematische Optimierung; Theorie